(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In a course of a study of bryophyte diaspore bank in the Rostov Botanical Garden (Russia), two common and one rare species (Acaulon triquetrum) were obtained. Plants of the latter species grown in culture did not possess any of the important diagnostic characters, which are usually seen in nature. However, a detailed study of leaf margin structure allowed us to identify these plants for sure. Diagnostic characters of A. triquetrum and its differentiation from the second species of the genus known in Russia are discussed.